The Impact Of Data Protection And Cyber Security On The Level Of Trust In Fintech In Bengkulu - Ikbal Wahyudi; Tito Irwanto; Lydia Gustina Putri (Jurnal Pusat Manajemen, 2026)
The purpose of this study was to determine the effect of data protection and cybersecurity on the level of trust in fintech use among the people of Bengkulu City. The theories used in this study consist of several theories according to the research variables, namely data protection, cybersecurity, and the level of trust in fintech use. This research method used quantitative descriptive research. The sample in this study was the people of Bengkulu City, whose population was taken from Dukcapil data. The sample in this study was 80 people, with the sampling technique in this study using purposive sampling. The data collection technique was a questionnaire with a Likert scale measurement. The data analysis technique used in this study was quantitative descriptive.The results of the study show multiple linear regression analysis with the equation Y = 5.203 + 0.463 X1 + 0.481 X2 + 4.332 shows a positive direction of the influence of data protection and cyber security on the level of trust in the use of fintech in Bengkulu society. Data protection influences the level of trust in the use of fintech in Bengkulu society with a calculated t value of 3.463 > t table 1.66488 and sig α = 0.001 < 0.05. Cyber ​​security influences the level of trust in the use of fintech in Bengkulu society with a calculated t value of 4.341 > t table 1.66488 and sig α = 0.000 < 0.05. Data protection and cybersecurity influence the level of trust in fintech among Bengkulu residents, with a coefficient of determination (R2) of 50.7% and an F-value of 37.405 > F-table of 3.12, with a significance level of 0.000 < 0.05.